1981
DOI: 10.1111/j.1476-5381.1981.tb09123.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxic and Inotropic Effects of Ouabain on Atria Isolated From Rabbits of Different Ages

Abstract: I In sino-atrial node-right atrial preparations and left atrial preparations obtained from rabbits of different ages (2 to 360 days old), cardiotoxic and inotropic effects of ouabain were compared. Tachyarrhythmias were produced in immature and mature rabbit right atria exposed for 6 to 8 min to ouabain (5 x 10-6 M). The total number of contractions before the arrhythmias developed varied inversely with age (2 to 90 days old). Percentage reductions in the resting membrane potential, overshoot and maximum rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
1985
1985

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Many authors have reported that the responsiveness of the heart to drugs or stress changes with age (Halloran, Schimoff, Nicholas & Talner, 1970;Rogers, Willerson, Goldblatt & Smith, 1972;Hayes, Butler & Cersony, 1973;Lakatta et al, 1975;Kelliher & Roberts, 1976;Guamieri et al, 1980;Toda, 1981;Hougen & Friedman, 1982). In the present study, the age-dependent differences in the positive inotropic effect of Phe have been observed in rat isolated atria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have reported that the responsiveness of the heart to drugs or stress changes with age (Halloran, Schimoff, Nicholas & Talner, 1970;Rogers, Willerson, Goldblatt & Smith, 1972;Hayes, Butler & Cersony, 1973;Lakatta et al, 1975;Kelliher & Roberts, 1976;Guamieri et al, 1980;Toda, 1981;Hougen & Friedman, 1982). In the present study, the age-dependent differences in the positive inotropic effect of Phe have been observed in rat isolated atria.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors including hormones (Nakashima et al, 1971(Nakashima et al, , 1973Kunos, Vermas-Kunos & Nickerson, 1974;Kunos, 1977; Hashimoto & Nakashima, 1978;Hirano, Hashimoto & Nakashima, 1982) and temperature (Endoh, Wagner & Schumann, 1975;Benfey, 1977;Mori, Hashimoto, Hasegawa & Nakashima, 1979) markedly affect the a-adrenoceptor-mediated positive inotropic effect. On the other hand, it has been reported that the responsiveness of the heart to drugs or stress vary with age (Shreiner, Weisfeld & Schock, 1969;Conway, Wheeler & Sannerstedt, 1971;Kronenberg & Drage, 1973;Lakatta, Gerstenblith, Angell, Schock & Weisfeld, 1975;Petrofsky & Lind, 1975;Toda, Fu & Osumi, 1976;Yin, Spurgeon, Raizes, Greene, Weisfeld & Schock, 1976;Gerstenblith, Spurgeon, Froehlich, Weisfeld & Lakatta, 1979;Yin, Spurgeon, Greene, Lakatta & Weisfeld, 1979;Guarnieri, Filburn, Zitnik, Roth & Lakatta, 1980;Toda, 1981). Lakatta et al (1975) and Guarnieri et al (1980) have demonstrated the diminished inotropic response to mature myocardium to catecholamines.…”
Section: Introductionmentioning
confidence: 99%